Financialization and deterritorialization in the Milanese major urban development projects - Alberto Bortolotti (PlaNext, 2025)
Major urban development projects are pivotal to connect financial and real estate markets through the ‘financialization’ of strategic lands and the ‘deterritorialization’ of actors, practices and instruments. Milan is currently facing several large-scale property operations delivered by global developers and investors. Among these, this article problematizes the Milano Innovation District (MIND) by reconstructing its spatial development, showing how property financialization generates a deterritorialization of this project from the city planning system.  Milan’s case has been considered relevant because of the convergence of global and local interest in developing the former Expo 2015 site, in a little metropolis which, on the other hand, shows an enormous concentration of financial capital managed in the Milanese headquarters of some of the largest European banks. In this article I will introduce the concept of financialization, which challenges land uses in this hyper-capitalization time, provide an illustration of the Milanese planning system, outline the interactions between planning, politics and finance, and present the case analysis of MIND and a discussion of its findings. In conclusion, this contribution remarks how such projects are used as levers to pursue polycentrism by challenging the ‘raison d’étre’ of statutory planning in overseeing the city’s urban growth instead of just enabling land value extraction, expansion and densification. Overall, the article argues that financialization has undermined redistribution of wealth through spatial planning, and this role has shifted to the major property corporations.